Socio-demographic and economic characterization of the poultry rural microentrepreneur - Sbaraini, Jair (Scientia Agraria Paranaensis, 2021)
Brazil’s predominant poultry production system is vertical integration, which has advantages for both sides, providing a constant income to farmers and a constant supply of raw material at competitive costs for the agroindustry. The study aimed to understand better the integrated farmers into the broiler production system in the microregions of Araraquara and São Carlos, totaling 17 cities in the interior of the state of São Paulo. The methodology consists of applying socio-demographic questionnaires in the region. It was observed that the properties have an average capacity for raising 36,120 birds in 2 aviaries in a built area of ​​3,398 m2. The workforce is predominantly male, white, married, and with children. In addition, 44.9% have only elementary education, while 22.5% have completed high school, and only 12.4% have higher education. 86.5% own their properties, while 7.9% are tenants. Also, 88.8% have an annual income of R360,000 from the activity, and 55.1% go to the sector to supplement their income. In addition, 43% do not have any financing, and 33% have no interest in investing more in the activity. The data found in the present study is more favorable than the socio-economic data of rural producers present in the literature, not that they are concerned with the conditions in which the broiler producers are inserted, which are mainly evidenced by the possession of the properties and the producer’s way of life. It was also found that many poultry producers have conservative profiles, using their resources, no financing, and with an aversion to taking risks.